Radiocarbon ages of sediment core samples from the Bay of Bengal (IEDA: EarthChem Library)
This dataset presents results from AMS-radiocarbon dating of planktonic foraminifera from sediment core samples collected during cruise SO93 on R/V Sonne in the Bay of Bengal. These data are used to refine age models for the sediment cores.